A comprehensive study of bioremediation for pharmaceutical wastewater treatment - Smer Lakhani; Diya Acharya; Rishi Sakariya; Devansh Sharma; Prachi Patel; Manan Shah; Mitul Prajapati (Cleaner Chemical Engineering, 2022)
Quality water is used for various daily chores like drainage, drinking, sanitation, agricultural, and other industrial applications, thus being the need of the hour. Water is a dominant raw material in manufacturing pharmaceuticals and chemicals; reliable and superior water sources are needed for many processes, including cooling, refining, and material extraction. The purpose of urban and industrial wastewater treatment is to eliminate contaminants, destroy toxicants, neutralise coarse particles, and destroy bacteria to increase the consistency of the discharged water to maintain the allowable amount of water to be discharged into or for agricultural property. So, the goal of water treatment is to lower BOD, COD, eutrophication, etc., in receiving water sources and stop radioactive compounds from spreading through the food chain. Pharmaceutical wastewater has a wide range of characteristics, including a high amount of organic matter, microbial contamination, a high salt content, and the inability to biodegrade. Following secondary application, residual quantities of suspended solids and dissolved organic matter exist. Therefore, advanced treatment is necessary to increase the efficiency of pharmaceutical wastewater effluent. In the methods described in this study, Advanced Oxidation and Bioremediation—the latter emerges as the most environmentally and commercially viable option. This paper discusses the many types of bioremediations, their applications, and their limits in the treatment of industrial wastewater with the goal of reducing the ecotoxicological impacts of pharmaceutical wastewater.